PENGARUH SELF EFFICACY DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL DENGAN MODERASI BUDAYA ORGANISASI (STUDI PADA PEGAWAI KECAMATAN EKS KAWEDANAN TEMANGGUNG KABUPATEN TEMANGGUNG) - 11.52.02.0107, Dewi Insan Kamil Pamungkas (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to analyze the influence of Self Efficacy and Transformational Leadership Style on Organizational Commitment with organizational culture as moderation. Respondent in this study is employee of sub district exs Kawedanan Temanggung. Population is this research is 204 person and the sample collection technique using purposive sampling criteria : a minimum level education past high school and year of service at least 3 years. The number of respondents who meet these criteria as 166 person. Test instruments use validity and reliability, while the model test use R2 test (coefficient of determination), F test (Goodness of Fit) and t-test (t-test). Hypothesis Testing in this research use the regression analysis with t count criteria. Hypothesis testing is used t count frequency distribution test at significance level (Î±) of 5%.The results showed (1) Self Efficacy has positive impact on Organizational Commitment, (2) Transformational Leadership Style has positive impact on Organizational Commitment, (3) The Organizational Culture does not moderated the effect of Transformational Leadership Style has positive impact on Organizational Commitment. Keywords: Self Efficacy, Transformational Leadership Style, Organizational Commitment, and Organizational Culture